TAFSIR PADA PEREMPUAN DALAM AL-QUR’AN SURAT AN-NISA’ - RENI YULIA AMBARWATI (Yinyang: Jurnal Studi Islam Gender dan Anak, 2017)
This paper describes gender equality in ancient timeswomen were despised by men is based on the creation of woman from therib of man. There were two things that were examined in this article. First,exposure on equality between men and women; Second, the role of womenand the position of women is no less influential than men. This paper seeksto provide a justification and an understanding of the old paradigm thatsays she was weak. This is because in the Qurâ€™an, especially in Suratan-Nisa â€˜explains about the creation of man and woman. Men and womenof Ù…Ù† Ù†ÙØ³ ÙˆØ§ØØ¯Ø©consists of one no differences from the human side. Godcreated both of these into a pair. In this case, male and female (Adam andEve) to be born a unity and cohesion.